2006
DOI: 10.3844/ajidsp.2006.49.57
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-Induces Differential Protein Expression by Normal Human Astrocytes (NHA)

Abstract: Heroin use is postulated to act as a cofactor in the neuropathogenesis of human immunodeficiency virus (HIV-1) infection. Astrocytes, integral components of the CNS, are reported to be susceptible to HIV-1 infection. Upon activation, astrocytes release a number of immunoregulatory products or modulate the expression of a number of proteins that foster the immunopathogenesis of HIV-1 infection. However, the role of heroin on HIV-1 infectivity and the expression of the proteome of normal human astrocytes (NHA) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Creatine kinase B was downregulated by TH in our study, and by alcohol [54,56,60]. ATP synthase beta-chain with lower expression level was detected in a number of substances of abuse such as morphine [13,58], heroin [21], nicotine [52,53], and alcohol [55] by proteomic study. 14-3-3 protein epsilon was reduced by alcohol [23,60], Table 5 -Summary of proteins modified by tramadol and one or more other substances of abuse.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Creatine kinase B was downregulated by TH in our study, and by alcohol [54,56,60]. ATP synthase beta-chain with lower expression level was detected in a number of substances of abuse such as morphine [13,58], heroin [21], nicotine [52,53], and alcohol [55] by proteomic study. 14-3-3 protein epsilon was reduced by alcohol [23,60], Table 5 -Summary of proteins modified by tramadol and one or more other substances of abuse.…”
Section: Discussionmentioning
confidence: 58%
“…Energy metabolism Aldolase C Nicotine [52,53]; Alcohol [23,56]; Amphetamine [57]; Butorphanol [24]; Cocaine [17]; Heroin [21]; Morphine [11,58,62]; ATP synthase beta-chain Nicotine [52]; Amphetamine [57]; Alcohol [23,55]; Cocaine [59]; Heroin [21]; Morphine [11,13,14,58]; Creatine kinase B Alcohol [23,[54][55][56]60]; Methamphetamine [61]; Cocaine [17];…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that treatment of IDC and astrocytes with methamphetamine and heroin, respectively, increase the expression of galectin-1 (21, 39). Therefore, we sought to determine whether morphine could modulate galectin-1 gene expression in human MDM.…”
Section: Resultsmentioning
confidence: 99%
“…The function of FAM3C is unknown, and it is unclear whether it is a secreted or a membrane protein. Tumor protein D54 has been identified by MS-based proteomics studies in normal human astrocytes (65), in breast tumor cells (66), and in lipid droplets from lipolytically stimulated (but not unstimulated) adipocytes (67). No studies of its physiological function have been reported.…”
mentioning
confidence: 99%